Textiles - Austoni, Beryl (Cambridge University Press, New York, 1996)
IT applications in a company - Skills and materials used to make shoes - History of Dr Martens - Doc Martens - Design and technology - Product planning - Skopos - Production of fabrics - History and manufacturing of Aquascutum - Socks - Peta Flint designs